A Study on Effect of Melatonin in Dyslipidemia Caused by Experimentally Diabetes - Deniz Uluışık; Ercan Keskin; Durmuş Hatipoğlu (Selcuk University, 2019)
In this study, it was aimed to determine the effects of melatonin application on lipid profile in streptozotocin-induced diabetic rats. Animals in control group were not any treatment. Melatonin group animals received 50 mg/kg melatonin intraperitoneally in daily for eight weeks. Diabetes was induced by subcutaneous injections of streptozotocin at dose of 40 mg/kg for two days as a single dose per day in diabetes group animals. Animals in Diabetes+Melatonin group were made diabetic by streptozotocin in the same way and then these animals received 50 mg/kg melatonin intraperitoneally in daily for eight weeks. In blood samples taken from all animals, TNF-α, triglyceride, total cholesterol, LDL and HDL were determined. In diabetes group, TNF-α level were high (p lt;0.05). The changes in TNF-α level with melatonin application to diabetic rats were important (p lt;0.05). In diabetic rats, triglyceride and LDL levels were found to be enhanced compared to control group (p lt;0.05), HDL level was significantly low (p lt;0.05), while the change in total cholesterol level was not important. With the melatonin application to diabetic rats, HDL level was found to be higher (p lt;0.05) and LDL level was lower than diabetes group (p lt;0.05). It was concluded that the administration of melatonin to streptozotocin-induced diabetic rats may have positive effects on lipid profile.